Penerapan Prinsip First To File Dalam Sengketa Merek Internasional Putusan Nomor : 106/Pdt.Sus-Merek/2023/PN.Niaga.Jkt.Pst. - Ramadhani, Astrid Puspita; Roisah, Kholis (Universitas Ekasakti, 2024)
Law Number 20 of 2016 concerning Trademarks and Geographical Indications regulates the legal protection trademarks in Indonesia. Trademark disputes in Indonesia still often occur, especially regarding trademark similarities. The trademark registration system that generally known is the constitutive system (First To File). The purpose of this paper is to find out how the first to file principle is applied in trademark disputes and the legal consequences of decisions on trademark disputes. The method used in this study is normative juridical. Based on the results of the study, even though a trademark has been registered for the first time, if it is proven that the trademark has exceeded its legal protection period of 10 years, the legal consequences are that anyone can use the trademark.